Model of Sharia Financing Contract in the Form of Notary Deed According to the Perspective of Islamic Law - Muhammad Syukran Yamin Lubis; Asmuni Asmuni; Mhd. Syahnan (Faculty of Law, Universitas Pekalongan, 2023)
The practice of developing sharia financing has actually experienced massive developments, especially in ensuring the existence of legal certainty in transactions. One of the developmental practices of sharia financing is the existence of a contract formulated in the form of a notarial deed. This research focuses on the legal vacuum related to the arrangement of making a shari'ah financing contract in the form of a notarial deed. This research is a normative legal research with a concept and statutory approach. The results of the study show that a sharia financing contract made in the form of a notarial deed according to Islamic law must still refer to the provisions of syar'i law. In the process of shari'ah financing contracts, it is necessary to refer to several syar'i aspects, such as paying attention to the provisions contained in the Qur'an and sunnah, the Sharia Banking Law, to the JN Law. The model for making sharia financing contracts in the form of a notary deed based on the principles of agreement in Islamic law places the position of a notary to guarantee neutrality, professionalism and integrity including fulfilling and complying with the code of ethics. Notaries need to understand the provisions of syar'i or Islamic law in formulating a syari'ah financing contract requiring certification and special training in making sharia banking contracts for notaries